Protocol for evaluation of Movember’s scaling what works grant funding program: Supporting the delivery of mental health interventions for men & boys in Australia, Canada and the United Kingdom - Thomas Steele; Chloe Ang; Vanessa Rose; Gayatri Kembhavi; Jamie Rowland; Maryanna Abdo; Janell Kwok; Katherine Young; Sophie Merryfull; Sara Whittaker; Natasha Brusco; Rhiannon Watt; et al. (PLoS ONE, 2026)
Background Mental ill health among men and boys is a significant global issue, with barriers to recognising symptoms, seeking help, and accessing services. In response, Movember launched the Scaling What Works (SWW) grant funding in 2022. This initiative supports 17 diverse mental health projects across Australia, Canada, and the UK, targeting communities, schools, and workplaces to address the varied needs and contexts of men and boys. Methods Our evaluation protocol outlines the approach to assessing the SWW program across four domains: implementation, effectiveness, cost (implementation and cost-effectiveness), and scalability. Using the Intervention Scalability Assessment Tool (ISAT) as a framework, we aim to embed scalability considerations into the evaluation design. Data will be collected qualitatively and quantitatively from project participants, facilitators, and Movember staff throughout the funding period. Effectiveness will be measured using the Personal Wellbeing Index (PWI) as a universal outcome across projects. Scalability will be assessed using a purpose-built tool developed in consultation with ISAT’s creator, tailored to project-specific needs. Conclusion This evaluation will provide insights into program effectiveness, implementation strategies, delivery costs, and cost-effectiveness. With a strong focus on scalability, it aims to inform mental health service providers and funders on best practices for scaling interventions within grant-funded contexts.